Outcome of Ticagrelor Versus Clopidogrel in ACS Patients Undergoing PCI - Bari, Abdul Manan; Raza, Mahzaib; Ijaz ul Haq; Saleem, Qaiser; Sofia; Anika (Indus Journal of Bioscience Research, 2024)
Objective: To compare the efficacy and safety of ticagrelor versus clopidogrel in reducing major adverse cardiovascular events (MACE) and managing bleeding risks in patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) at Pakistan Atomic Energy Commission of Pakistan. Methodology: This prospective, randomized study included 400 ACS patients undergoing PCI from January 2023 to August 2024. Patients were divided into two groups, receiving either ticagrelor (n=200) or clopidogrel (n=200), with outcomes assessed at 30 days. The primary outcome was the occurrence of MACE, and secondary outcomes included minor bleeding events and stent thrombosis rates. Data were analyzed using chi-square tests to compare efficacy and safety between groups. Results: Ticagrelor showed a slightly lower rate of MACE (49%) compared to clopidogrel (55%), suggesting enhanced efficacy in reducing ischemic events. However, ticagrelor also had a higher incidence of minor bleeding events (56.5% vs. 47% in the clopidogrel group), underscoring the need for careful patient selection due to increased bleeding risks. Stent thrombosis rates did not differ significantly between the groups. Conclusion: Ticagrelor provides a beneficial alternative to clopidogrel for preventing ischemic events in ACS patients undergoing PCI. However, due to its higher bleeding risk, individualized patient assessment is crucial to optimizing outcomes. These findings contribute essential evidence to guide antiplatelet therapy in the Pakistani context.